(untitled) (Journal of International English Research Studies (JIERS), ISSN: 3048-5231, 2024)
This study explores the phenomenon of code-switching within multilingual communities, focusing on case studies from Kenya, Malaysia, and the United Arab Emirates (UAE). In these culturally diverse nations, code-switching serves as a vital linguistic strategy that reflects complex social dynamics, identity construction, and communicative efficiency. Drawing on sociolinguistic fieldwork, interviews, and discourse analysis, the research examines how individuals navigate between languages such as English, Swahili, Arabic, Malay, and various regional or expatriate tongues. The findings reveal that code-switching in Kenya often aligns with socio-political contexts and urban-rural language practices; in Malaysia, it functions as a tool for negotiating ethnic identity and social cohesion; and in the UAE, it underscores class distinctions and intercultural interactions within its expatriate-majority population. This comparative analysis highlights how code-switching is both a linguistic and social resource, shaped by historical legacies, education systems, and shifting demographics. The study contributes to broader discussions on multilingualism, linguistic hybridity, and the evolving role of language in postcolonial and globalized societies.